Diffusion and lifetime modeling for slurry aluminide coating on P92 at 650 °C with a computational and experimental approach. Issue 12 (27th June 2016) - Krukovskyi, P.; Metel, M.; Agüero, A.; Muelas, R.; Kolarik, V.
Abstract : The present work is devoted to the estimation of the coating lifetime by modeling aluminum diffusion in a slurry‐applied coating on P92 at 650 °C employing the computational and experimental approach. This coating protects ferritic steels from both steam and fireside corrosion on new coal‐fired power plants operating under super‐supercritical steam parameters. The computer model of the diffusion and oxidation based on a numerical solving of the differential equations of diffusion was developed, and its unknown parameters, namely the concentration‐dependent aluminum diffusion coefficient, were identified from relatively short‐term experimental tests up to 8000 h using the inverse problem solution approach. The model was then used for coating lifetime estimation and furthermore for obtaining the dependency of the lifetime on the initial coating thickness and on the critical beneath‐surface aluminum content defined for the estimation. The resulting simulated concentration profiles were compared with experimental data yielding an adequate fit. Abstract : The paper presents the developed model of the studied slurry aluminide coating on the P92 substrate tested in steam atmosphere at 650 °C, the proposed computational and experimental approach, results of modeling compared to the experimental data and the lifetime estimations depending on the coating thickness and critical aluminum content.